Niger - Modernizing Trade During a Mining Boom : Diagnostic Trade Integration Study for the Integrated Framework Program - World Bank (World Bank, 2012)
The Niger Diagnostic Trade Integration Study (DTIS) has been prepared under the Integrated Framework (IF) for trade related technical assistance to least developed countries in response to a request from the Government of Burkina Faso. The study is to build the foundation for accelerated growth by enhancing the integration of its economy into regional and global markets. This Diagnostic Trade Integration Study (DTIS) is intended to provide a broad overview of the key elements for successful integration into external markets, both through access to low-cost imports and especially through the development and diversification of exports. It pays particular attention to the role that trade can play in poverty reduction. It is fully in line with Niger's new strategy for accelerated development and poverty reduction. Indeed, that strategy refers to this study as a key input and identifies the same set of priority sectors as sources of growth - rural development, artisanal crafts, tourism and mining. This study is also consistent with the rural development strategy which emphasizes various export-oriented agro-pastoral subsectors. What this study to do is to provide more details and a sense of priorities in order to strengthen the trade component of these two strategies.